Analysis and optimization of gyrokinetic toroidal simulations on homogenous and heterogenous platforms. (November 2013) - Ibrahim, Khaled Z; Madduri, Kamesh; Williams, Samuel; Wang, Bei; Ethier, Stephane; Oliker, Leonid
The Gyrokinetic Toroidal Code (GTC) uses the particle-in-cell method to efficiently simulate plasma microturbulence. This work presents novel analysis and optimization techniques to enhance the performance of GTC on large-scale machines. We introduce cell access analysis to better manage locality vs. synchronization tradeoffs on CPU and GPU-based architectures. Our optimized hybrid parallel implementation of GTC uses MPI, OpenMP, and NVIDIA CUDA, achieves up to a 2× speedup over the reference Fortran version on multiple parallel systems, and scales efficiently to tens of thousands of cores.